Two new species of Cephalops Fallén (Diptera: Pipunculidae) from Colombia, and an updated key to males of the Neotropical species - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Wolff, Marta (Zootaxa, 2025)
Cephalops Fallén, 1810 has a cosmopolitan distribution. Two new species of Cephalops are here described from protected areas of Colombia, namely Cephalops baldiensis sp. nov. (type locality: Páramos Baldías, Antioquia) and C. farallonensis sp. nov. (type locality: Parque Nacional Natural Farallones de Cali, Valle del Cauca). With this paper, the number of Cephalops species from the Neotropical Region increase from 17 to 19 and in Colombia from 5 to 7. Illustrations of the new species, dichotomous key to males and a distribution map of the Colombian species is presented.